Limitations and Opportunities in Open Laryngeal Organ Preservation Surgery: Current Role of OPHLs - Succo, Giovanni; Crosetti, Erika (Frontiers in Oncology, 2019)
The current trend for treatment of intermediate-early advanced laryngeal cancer is essentially oriented toward preservation of organ and laryngeal function, and with a good potential for treating the disease. This goal can be achieved by adopting open laryngeal organ preservation surgery (OLOPS), at present mainly represented by open partial horizontal laryngectomies (OPHLs). An approach using rigorous selection criteria based on both the general condition of the patient and the local and regional extent of the disease gives excellent oncological and functional results in untreated patients. Similar outcomes, albeit slightly worse, are also obtainable in radio-recurrent and laser-recurrent patients. Troublesome postoperative management and the inconsistency of functional recovery are the main limitations for extensive application of this therapeutic strategy. The future direction is represented by simplification of the indications identifying iso-prognostic sub-categories within the T-stage, wider consensus on rehabilitation protocols, hybrid approaches to the larynx, and open minimally invasive access.